Exploring Responsible Project Management Education - Gilbert Silvius; Ron Schipper (MDPI AG, 2018)
As projects are evolving from tactical level ‘tasks’ to societally-relevant ‘instruments of change’, the theories, methods, and practices of project management need to evolve, too. Academic programs on project management, logically, should be frontrunners in this development, which calls for societally-relevant and ‘responsible’ project management education. Following the model of the United Nations Principles for Responsible Management Education, some first ideas on what Responsible Project Management Education should entail developed. The study presented in this article uses meta-synthesis to explore the meaning and characteristics of responsible project management education. The study concludes nine characteristics that provide a conceptual starting point for more empirical research on the topic.